Safety, Pharmacokinetics and Pharmacodynamics of Gs-9620, An Oral Toll-Like Receptor 7 Agonist. Issue 3 (April 2013) - Lopatin, Uri; Wolfgang, Grushenka; Tumas, Daniel; Frey, Christian R; Ohmstede, Carol; Hesselgesser, Joseph; Kearney, Brian; Moorehead, Lisa; Subramanian, G Mani; McHutchison, John G
Background: GS-9620 is a novel oral agonist of Toll-like receptor 7 (TLR7) in development for the treatment of chronic viral hepatitis. TLR7 is a highly conserved innate immune receptor expressed primarily on plasmacytoid dendritic cells and B lymphocytes. The aim of this double-blind, placebo-controlled, single ascending-dose study was to investigate the safety, tolerability, pharmacokinetics and pharmacodynamics of GS-9620 in healthy volunteers. Methods: In total, 75 healthy volunteers (8 subjects in each of the 10 cohorts; 5 subjects participated in two cohorts) were randomized (6:2) to receive a single dose of GS-9620 (0.3, 1, 2, 4, 6, 8 or 12 mg) or placebo. Results: GS-9620 was well-absorbed and well-tolerated in oral doses up to 12 mg. Minimal treatment-related adverse events were seen at doses up to 8 mg. Serum interferon (IFN)-α was only detected in subjects who received 8 or 12 mg doses, and the adverse event profile at 8 and 12 mg doses was generally consistent with that associated with IFN-α exposure (flu-like symptoms), consistent with the mechanism of TLR7 agonism. All adverse events resolved within 72 h. Induction of chemokines/ cytokines and IFN-stimulated genes were seen at GS-9620 doses ≥2 mg, well below doses that induced serum IFN-α or led to clinical adverse events. Conclusions: GS-9620 demonstrates safety and pharmacodynamic activity at doses up to 12 mg. Pharmacodynamic activity is seen before adverse events, suggesting the potential for induction of an antiviral response without systemic adverse events in subjects with chronic viral hepatitis.